Transparent Schottky Photodiode Based on AgNi NWs/SrTiO3 Contact with an Ultrafast Photoresponse to Short‐Wavelength Blue Light and UV‐Shielding Effect. (1st September 2019) - Yang, Wei; Zhang, Yong; Zhang, Yujia; Deng, Wanjun; Fang, Xiaosheng
Abstract: A transparent Schottky photodiode is constructed based on a SrTiO3 (STO) wafer, in which nickel‐coated silver nanowires (AgNi NWs) are proposed as the high‐work‐function transparent electrode. A selective photoresponse to harmful short‐wavelength blue (SWB) light is generated owing to the proper bandgap of STO, and the AgNi NWs effectively strengthen the photovoltaic behavior, resulting in an ultrafast response speed ( t rise / t fall = 7 µs/115 µs) and photocurrent of 16–38 nA under a 0 V bias. Meanwhile, the complete device maintains a transparency of ≈60% almost over the entire visible light region and blocks 96.7% UVA and >99.9% UVB. The combination of bias‐free SWB detection and transparent UV shielding is readily applicable to protect against light pollution. Furthermore, this work proposes a considerable method to modulate the work function of transparent Ag NW electrodes by surface coating, which provides inspiration for the development of transparent electrode materials with different work functions. Abstract : Nickel‐coated silver nanowires (NWs) are prepared for high‐work‐function transparent electrodes, based on which a SrTiO3 ‐based transparent Schottky photodiode is reported. The device simultaneously combines a bias‐free photodector for harmful short‐wavelength blue light and a transparent UV filter, which is very suitable to fight against light pollution. Meanwhile, a considerable surface‐coating method is proposed to modulate the work function of transparent Ag NW electrodes.